2018
DOI: 10.1253/circj.cj-18-0619
|View full text |Cite
|
Sign up to set email alerts
|

Different Neointimal Pattern in Early vs. Late In-Stent Restenosis and Clinical Outcomes After Drug-Coated Balloon Angioplasty ― An Optical Coherence Tomography Study ―

Abstract: DCB angioplasty is less effective for heterogeneous neointima in DES ISR. OCT-based neointimal evaluation may be helpful in guiding treatment of DES ISR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…Interestingly, these data are consistent with previous reports: A recent intravascular imaging study reporting of numerically higher MACE rates in patients with early ISR as compared to patients with late ISR undergoing DCB treatment. Noteworthy, the presence of a heterogeneous neointima was an independent predictor of MACE in this analysis and was reported in almost 30% of patients presenting with early ISR 21 . In line, Zhao et al reports a significant higher clinical event‐rates (MACE) in patients with early‐ISR, mainly driven by higher TLR rates, in patients with DES‐ISR treated with new‐generation DES 22…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, these data are consistent with previous reports: A recent intravascular imaging study reporting of numerically higher MACE rates in patients with early ISR as compared to patients with late ISR undergoing DCB treatment. Noteworthy, the presence of a heterogeneous neointima was an independent predictor of MACE in this analysis and was reported in almost 30% of patients presenting with early ISR 21 . In line, Zhao et al reports a significant higher clinical event‐rates (MACE) in patients with early‐ISR, mainly driven by higher TLR rates, in patients with DES‐ISR treated with new‐generation DES 22…”
Section: Discussionsupporting
confidence: 77%
“…[ 27 , 28 ] The serum lipid profile might affect the neointimal plaque characteristics and outcomes after PCI. In accordance with previous OCT studies which have found a lower cholesterol level and heterogeneous intima in the E-ISR group, [ 23 , 29 ] our data also show that low-density lipoprotein cholesterol (LDL-C) concentrations differ significantly between the E-ISR and L-ISR groups (2.0 [1.3–2.4] mmol/L vs . 2.3 [1.8–2.9] mmol/L, P = 0.035), and the total cholesterol (TC) tends to be numerically higher in the L-ISR group than the E-ISR group (3.8 [3.3–4.7] mmol/L vs .…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, heterogeneous neointima had been closely associated with higher target lesion failure rates in non-significant lesions not subjected to any interventions [1,9] and significant ISR lesions treated with DCB compared to non-heterogeneous neointima [2,3]. This study reported that 1) the incidence of TLR and non-TLR differed according to the in-stent neointimal characteristics and 2) patients with heterogeneous neointima with DESs were associated with a higher incidence of non-TLR and TLR.…”
Section: Discussionmentioning
confidence: 53%
“…The stent and luminal cross-sectional area (CSA) were analyzed, and the neointimal CSA was calculated as the stent CSA minus the luminal CSA. The segment with minimal lumen area (MLA) and maximal neointimal proliferation was considered the representative site of lesions for future clinical follow-up [1,2]. Therefore, the stented segments at the minimal lumen CSA and maximal neointimal CSA were qualitatively assessed to characterize the neointimal tissue as either homogeneous (a uniform signalrich band without focal variation or attenuation), heterogeneous (focally changing optical properties and various backscattering patterns), or layered neointima (layers with different optical properties, namely, an adluminal high-scattering layer and an abluminal low-scattering layer) [4].…”
Section: Analysis Of Coronary Angiography and Oct Imagesmentioning
confidence: 99%
See 1 more Smart Citation